Beyond market penetration: leveraging brand capital for competitive advantage in digitally driven SMES in resource-constrained settings - Rennie Bakashaba; Dedrix Stephenson Bindeeba (Future Business Journal, 2025)
Digital commerce activation (DCA) has enabled SMEs to broaden market reach, yet market penetration (MP) alone often fails to create sustainable competitive advantage (CA). Drawing on the Resource-Based View and Dynamic Capabilities Theory, this study examines how brand capital (BC) mediates the relationship between DCA and CA while assessing MP’s parallel role. Survey data were collected from 405 digitally active SMEs in Kampala and Wakiso, Uganda, and analyzed through structural equation modeling. Findings indicate that DCA significantly enhances both BC and MP; however, MP neither directly influences CA nor transmits DCA’s effects into CA. In contrast, BC dem onstrates a strong positive influence on CA and fully mediates the DCA–CA relationship. These results confirm that BC, encompassing brand awareness, perceived quality, loyalty, and associations, functions as a valuable, rare, inimitable, and non-substitutable (VRIN) resource that converts digital investments into enduring advantage. The study contrib utes by (1) extending RBV to position BC as the primary intangible conduit for digital strategy, (2) clarifying the micro foundations of BC formation via dynamic digital routines, and (3) offering context-specific insights for resource-con strained SMEs. Practically, managers should prioritize brand-building routines over reach-seeking, and policymakers should support digital branding initiatives to strengthen SME competitiveness.
Keywords: Digital commerce activation; Brand capital; Market penetration; Competitive advantage; SMEs; Resource constrained environments; Uganda